A switchable electrochromism and electrochemiluminescence bifunctional sensor based on the electro-triggered isomerization of spiropyran/layered double hydroxides. Issue 63 (24th July 2017) - Li, Zhixiong; Zhou, Yuqiong; Peng, Liuqi; Yan, Dongpeng; Wei, Min
Abstract : A bifunctional ultrathin film electrode was fabricated based on layered double hydroxides and spiropyran, which exhibited electrochromism and electrochemiluminescence sensing behavior toward temperature and Zn 2+ ions. Abstract : A bifunctional ultrathin film (UTF) electrode was fabricated based on layered double hydroxides (LDHs) and spiropyran (SP), which exhibited electrochromism and electrochemiluminescence (ECL) sensing behavior toward temperature and Zn 2+ ions.